PENGEMBANGAN TES PENGETAHUAN GAMBAR TEKNIK BERBASIS WEBSITE - Sella Kurniawati; Soeprijanto; Farried Wadjdi (Fakultas Teknik Universitas Negeri Jakarta, 2017)
This Research and development determines the effectiveness of media usage test based on website when compared with conventional test, for the final exam related to basic knowledge of engineering drawings on electrical engineering major of a vocational school called Teknik Instalasi Pemanfaatan Tenaga Listrik (TIPTL). The research was conducted at SMKN, a public vocational high school, from August 2016 until December 2016. The method used in this research is Research and Development while the ADDIE model (Analysis, Design, Development, Implentation, and Evaluation). The data was collected by using a questionnaire for measuring the feasibility of the media and the effectiveness formula is used to determine the effectiveness of aformentioned media. Based on research that has been conducted, the test of testing by subject matter experts indicate that the product got 92%, the results of testing by media experts got 89%, and the results of testing by students 88%. Then, the development of knowledge technical drawing test based on website can be expressed very worthy to be used. The results of the comparing the efficacy score between web-based test with conventional test shows, the effectiveness score of conventional test (ETK) is 0.015, and the effectiveness score of web-based test (ETBW) is 0.12. Based on that comparison <